Photobiomodulation vs NSAIDs in the management of postoperative dentoalveolar pain - Alaa Alqutub; Mona Rajeh; Sarah Almuwallad; Haefa Alghamdi; Nidaa Bifari; Rahaf Aljabri; Ruba Zainialmutwkkil; Abdalmalik O. Ghandourah (Saudi Dental Journal, 2022)
Background: Postoperative pain, the most common complication of dentoalveolar surgery, is routinely controlled by non-steroidal anti-inflammatory drugs (NSAIDs). However, despite its proven efficacy, the long-term consumption of NSAIDs is associated with several serious and adverse effects. As a result, photobiomodulation (PBM) or low-level laser therapy (LLLT) is used in many treatment modalities to reduce pain, inflammation, and promote healing. Aim of the study: To compare the analgesic effects of LLLT and Ibuprofen after surgical dental extraction. Materials and methods: A clinical trial study was conducted at Umm Al-Qura University Dental Clinics, involving 46 healthy patients between 20 and 60 years of age. The recruited patients were divided into two groups of 23 patients each. Group 1 (positive control group) was prescribed Ibuprofen and Group 2 (experimental group) was treated with LLLT. The pain was measured on days 1, 2, and 7 using the Numeric Pain Rating Scale (NPRS). Results: The mean level of pain decreased with both treatments. On the first postoperative day, the pain level in the laser therapy group was significantly lower than in the control group (U = 62.5, p = 0.024). The results indicated a significant decrease in pain level on the second postoperative day for both the control and experimental groups (Z = −3.61, p < 0.005, and Z = −3.1, p = 0.002, respectively). However, the pain level was lower in the control group, although the difference was not statistically significant (U = 79, p = 0.102). Conclusion: Considering the constraints of this study, NSAIDs were found to be significantly better at reducing pain than LLLT.